Design matters in home visiting improvement - Babyar, Julie Christine (International Journal Of Community Medicine And Public Health, 2017)
Maternal and child health home visiting services play a critical role in healthcare within the United States. Programs are widely varied and services offered depend on local and regional adopted designs. Observational and experimental research provides mixed conclusive results. Some literature reports statistically significant positive outcomes for home visitation services while other research fails to duplicate or provide secondary matched findings. Future research design opportunities include national, inclusive, cross collaborative home visiting research that seeks to minimize limitations. Future home visiting programs should utilize research opportunities in public and private program redesign, continuous quality improvement as well as in accreditation for optimal effect on target populations. Only with strong, supportive research can maternal and child home visiting services be tailored, replicated and consistent across the United States.